THE IMPACT OF GEOGRAPHICAL INDICATION TAGGING ON KASHMIRI SAFFRON: AN EMPIRICAL EVALUATION - Alam, Mir Junaid; Basharat, Heena; Bhat, Iftikhar Hussain; Kumar, Saima Ahad (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Geographical Indications (GIs) serve as a powerful tool for safeguarding the authenticity and heritage of regional products, while also fostering socio-economic development. Kashmiri saffron, a globally renowned GI-tagged product, symbolizes the rich agricultural tradition and cultural identity of the Kashmir Valley. The GI tag ensures the preservation of its unique characteristics—distinctive aroma, deep color, and medicinal properties—while protecting it from adulteration and market exploitation. The recognition not only enhances the product’s global marketability but also uplifts the livelihood of local farmers by ensuring premium pricing. Moreover, the GI status strengthens the Kashmiri saffron industry’s resilience against challenges like climate change and unfair competition, promoting sustainable agricultural practices. This paper explores the socio-economic implications of the GI certification for Kashmiri saffron, highlighting its role in preserving biodiversity, promoting rural development, and fostering equitable economic growth, thereby reinforcing its significance as both a cultural emblem and a driver of regional prosperity.